2021
DOI: 10.3390/ma14185336
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Post-Weld Heat Treatment on Microstructure and Toughness Properties of 13MnNiMoR High Strength Low Alloy Steel Weld Joint

Abstract: Weld and base metals require hot or cold working during the steel equipment manufacturing process. As a result, the components should be subjected to a normalizing heat treatment in order to recover their mechanical properties. In this study, the submerged-arc welding of the high strength low alloy (HSLA) thick steel plate(13MnNiMoR) is adapted for the vessel head under the normalizing and tempering heat treatment. The findings showed that the material toughness decreases after heating to simulate a vessel hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Xie et al [ 5 ] introduced a tempering process at low temperature and found that the toughness was significantly improved due to the decomposition of the MA constituent. Intercritical normalizing between normalizing and tempering was investigated to refine MA constituents, and a significant toughness enhancement was achieved [ 6 , 7 ]. Luo et al [ 8 ] applied ausforming to enable the microstructure modification of an MA constituent, and concluded the ausforming contributed to the austenite formation within the MA constituent, which was helpful in improving the toughness.…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al [ 5 ] introduced a tempering process at low temperature and found that the toughness was significantly improved due to the decomposition of the MA constituent. Intercritical normalizing between normalizing and tempering was investigated to refine MA constituents, and a significant toughness enhancement was achieved [ 6 , 7 ]. Luo et al [ 8 ] applied ausforming to enable the microstructure modification of an MA constituent, and concluded the ausforming contributed to the austenite formation within the MA constituent, which was helpful in improving the toughness.…”
Section: Introductionmentioning
confidence: 99%